The Importance of Strategic Entrepreneurship in Developing the Competitive Advantage of Enterprises – the Perspective of Agility - Sajdak, Maja (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The purpose of this paper is to identify the relationship between strategic entrepreneurship (according to the measures of this construct adopted) and competitive advantage (taking into account the market results of enterprises).Research Design & Methods: Quantitative research carried out on a sample of 424 medium-sized and large companies in Poland is the basis for the empirical conclusions. CATI (Computer Assisted Telephone Interview) was used to collect the data.Findings: Analysis of the results shows that all of the relationships analysed are positive and statistically significant. The main hypothesis, that there is a positive relationship between strategic entrepreneurship (co-created by: ability to cooperate, innovation ability, entrepreneurial culture) and the competitive advantage of enterprises, could not be rejected.Implications / Recommendations: The results could be extremely useful in developing strategic entrepreneurship in enterprises, providing an answer to the question of what makes some enterprises more effective than others in building a competitive advantage in terms of agility. The results of the research can be used by managers to make decisions concerning the shaping of attitudes and the behaviour of employees and the applicable standards in the context of differentiating the effectiveness of their correlation with the market results of enterprises.Contribution: The contribution of research results to the development of the scientific discipline can be indicated in the area of new knowledge on the different role of the dimensions of strategic entrepreneurship that differentiate the effectiveness of the company’s activities in the context of competitive advantage.